The politics of growth models and populism in East-Central Europe - Gábor Scheiring (economic sociology. perspectives and conversations, 2023)
The simultaneous rise of populism and the decay of liberal democracy in East-Central Europe is in striking contrast to the optimism prevalent in previous decades about the region's future. Without exception, each country in East-Central Europe embraced a dependent export-led growth model in the 1990s.
Keywords: 300